Human Rights Threats from the Tourism and Service Sector - Jindapol, Phuchongkorn (Journal of Cultural Approach, 2023)
The tourism and service sector is a large industrial sector that is involved in many sectors, whether public or private, that must coordinate and work together to achieve efficiency and good results as a whole. The influx of tourists will surely positively affect the economy, causing the tourism and service industry entrepreneurs to have increased revenues. There was growth in the economy, which was considered a huge income per country. At the same time, business competition arose in which entrepreneurs competed for dominance and wanted to gain market share as a monopoly. This causes human rights threats to tourists, both directly and indirectly. Both knowing and not knowing are all causes of a negative image of the tourism and hospitality industries because they cause tourists to worry, fear, suspicion, and feel insecure about their bodies and property. All of these things have not been mentioned or encouraged to create ways to prevent and protect tourists as they should be. Most of them will be fixed at the end of the cause. Without studying and getting to know the problem in depth, find a concrete way to prevent and solve it. This article, therefore, focuses on human rights threats from the tourism and service sectors that are the main causes of the negative attitude of tourists. It focuses mainly on situations where service providers interact directly with tourists in the purchase of goods and services. To be a guideline for prevention and to be developed as a concrete form of regulation in the future.